1997
DOI: 10.1111/1468-0297.00260
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and Economic Performance

Abstract: If a nation's economic performance improves, how much extra happiness does that buy its citizens? Most public debate assumes --without real evidence --that the answer is a lot. This paper examines the question by using information on well-being in Western countries. The data are of four kinds: on reported happiness, on reported life satisfaction, on reported job satisfaction, and on the number of suicides. These reveal patterns that are not visible to the anecdotal eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
234
0
15

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(261 citation statements)
references
References 35 publications
12
234
0
15
Order By: Relevance
“…An early meta-analysis (Haring, Stock, & Okun, 1984) found that males tend to report better well-being, while longitudinal studies also concluded that marriage supported psychological well-being (Kim & McKenry, 2002;Mentzakis, McNamee, Ryan, & Sutton, 2011). Similarly, increased well-being is commonly associated with higher absolute and relative income (Clark & Oswald, 1996;Mentzakis & Moro, 2009;Oswald, 1997), although consistent indicators for the latter are hard to identify. Finally, a strong positive link between better physical and mental health is reported consistently in 9 previous studies (Clark & Oswald, 2002;Mentzakis, 2011), although potential adaptation effects cannot be controlled for in our cross-sectional setting (Groot, 2000;Heyink, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…An early meta-analysis (Haring, Stock, & Okun, 1984) found that males tend to report better well-being, while longitudinal studies also concluded that marriage supported psychological well-being (Kim & McKenry, 2002;Mentzakis, McNamee, Ryan, & Sutton, 2011). Similarly, increased well-being is commonly associated with higher absolute and relative income (Clark & Oswald, 1996;Mentzakis & Moro, 2009;Oswald, 1997), although consistent indicators for the latter are hard to identify. Finally, a strong positive link between better physical and mental health is reported consistently in 9 previous studies (Clark & Oswald, 2002;Mentzakis, 2011), although potential adaptation effects cannot be controlled for in our cross-sectional setting (Groot, 2000;Heyink, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Subjective questions on self-reported well-being have been used in economics to understand and explore a large range of interesting topics, such as unemployment, health, job situation, and income (Blanchflower and Oswald, 2004;Clark and Oswald, 1994;DiTella et al, 2001;Easterlin, 2001;Ferreri-Carbonell, 2005;Ferrer-i-Carbonell and Frijters, 2004;Ferrer-i-Carbonell and Van Praag, 2002;Frey and Stutzer, 2002;Frijters et al, 2004;Oswald, 1997;Van Praag and Ferrer-i-Carbonell, 2004). In doing so, economists take individuals answer to well-being questions as a proxy to measure utility (see, e.g.…”
Section: The Well-being Modelmentioning
confidence: 99%
“…Oswald (1997). Further empirical evidence on the importance of relative concerns can be found in Robert H. Frank (1985a); Huib van de Stadt et al (1985); Andrew E. Clark and Andrew J.…”
mentioning
confidence: 98%